2019
DOI: 10.1128/aac.00543-19
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Cyp51 Contribution to Azole Resistance in Aspergillus Section Nigri

Abstract: Invasive aspergillosis (IA) is a severe condition mainly caused by Aspergillus fumigatus, although other species of the genus, such as section Nigri members, can also be involved. Voriconazole (VRC) is the recommended treatment for IA; however, the prevalence of azole-resistant Aspergillus isolates has alarmingly increased in recent years, and the underlying resistance mechanisms in non-fumigatus species remain unclear. We have determined the in vitro susceptibility of 36 strains from section Nigri to VRC, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(69 reference statements)
2
6
1
Order By: Relevance
“…A. tubingensis, A. welwitschiae and A. luchuensis/awamori in section Nigri also responded to high MICs of ITR (>16 μg ml −1 ). The considerable prevalence of A. tubingensis and some other cryptic species with different antifungal susceptibility patterns in clinical samples, which was observed here and in other studies from different countries [39][40][41], emphasizes the importance of the correct identification of Aspergillus species.…”
Section: Discussionsupporting
confidence: 79%
“…A. tubingensis, A. welwitschiae and A. luchuensis/awamori in section Nigri also responded to high MICs of ITR (>16 μg ml −1 ). The considerable prevalence of A. tubingensis and some other cryptic species with different antifungal susceptibility patterns in clinical samples, which was observed here and in other studies from different countries [39][40][41], emphasizes the importance of the correct identification of Aspergillus species.…”
Section: Discussionsupporting
confidence: 79%
“…For A. fumigatus , A. flavus , A. niger and A. terreus , they are in general susceptible to amphotericin B, itraconazole and voriconazole. Although azole resistance has been reported for these Aspergillus species, it is still relatively uncommon 27‐30 . However, in this study, we observed that a number of the rare/cryptic Aspergillus species isolates do not possess similar antifungal susceptibility patterns as the classical pathogenic Aspergillus species.…”
Section: Discussioncontrasting
confidence: 53%
“…In agreement with previous studies [ 3 , 34 ], Aspergillus alliaceus ( flavus complex) and Aspergillus tubingensis ( niger complex) show a variable susceptibility against azoles; A. alliaceus also yielding elevated MICs against amphotericin B. Ibrexafungerp was mostly inactive against A. alliaceus , as 75% (by EUCAST) and 40% (by CLSI) of the total number of isolates tested showed MECs > 2 mg/L. When tested in vitro against A. flavus strains in previous studies, this new drug did not display a homogenous effectiveness, being reported as active in some studies, with MEC values ranging from 0.06 mg/L to 0.25 mg/L [ 14 , 16 ], but as inactive in another (MEC range 2–16 mg/L) [ 15 ].…”
Section: Resultssupporting
confidence: 94%